2005
DOI: 10.1021/ja0562043
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-Controlled Asymmetric Synthesis of Fostriecin and 8-epi-Fostriecin

Abstract: Catalytic asymmetric synthesis of the natural antibiotic fostriecin (CI-920) and its analogue 8-epi-fostriecin and evaluation of their biological activity are described. We used four catalytic asymmetric reactions to construct all of the chiral centers of fostriecin and 8-epi-fostriecin; cyanosilylation of a ketone, Yamamoto allylation, direct aldol reaction, and Noyori reduction, two of which were developed by our group. Catalytic enantioselective cyanosilylation of ketone 13 produced the chiral tetrasubstitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(45 citation statements)
references
References 45 publications
2
40
0
3
Order By: Relevance
“…Cross-assay comparisons are particularly interesting since IC 50 values for fostriecin inhibition of PP2A are not only dependent on the assay enzyme concentration, but also the phosphorylated substrate used in the assay. 7,9 In preceding efforts related to the fostriecin family of natural products, we determined the stereochemical configuration of fostriecin (2) and reported its first total synthesis. 10 Subsequent to this work, a number of additional synthetic efforts have been described including eight total or formal syntheses of 2, each highlighting the utility of alternative asymmetric synthetic methods for the construction of the 4 chiral centers of 2 in a stereoselective manner.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-assay comparisons are particularly interesting since IC 50 values for fostriecin inhibition of PP2A are not only dependent on the assay enzyme concentration, but also the phosphorylated substrate used in the assay. 7,9 In preceding efforts related to the fostriecin family of natural products, we determined the stereochemical configuration of fostriecin (2) and reported its first total synthesis. 10 Subsequent to this work, a number of additional synthetic efforts have been described including eight total or formal syntheses of 2, each highlighting the utility of alternative asymmetric synthetic methods for the construction of the 4 chiral centers of 2 in a stereoselective manner.…”
Section: Introductionmentioning
confidence: 99%
“…Following the first total synthesis of fostriecin (Boger et al, 2001), at least nine total or formal syntheses have been reported (Chavez and Jacobsen, 2001;Esumi et al, 2002;Reddy and Falck, 2002;Miyashita et al, 2003;Maki et al, 2005;Trost et al, 2005). The total synthesis of cytostatin (Bialy and Waldmann, 2004;Lawhorn et al, 2006;Jung et al, 2008) and cytostatin analogs (Lawhorn et al, 2006;Jung et al, 2008) have also been reported.…”
mentioning
confidence: 99%
“…The heteropolymetallic catalyst LLB-KOH (70) was used in order to shorten the reaction times by enhancing the catalytic activity of LLB complex, giving aldol adducts 69a-d in modest to good enantioselectivities (Scheme 11). 30 Shibasaki and co-workers 31 reported the use of (S)-LLB (74) catalyst in the formal total synthesis of fostriecin (75) and 8-epi-fostriecin (8-epi-75). The best reaction condition to the system of interest for fostriecin (75) afforded the aldol adduct 73 in good yield using ketone 71 and aldehyde 72 and the two-center Lewis acid-Brønsted base catalyst (S)-LLB (74) (Scheme 12).…”
Section: Metal-catalyzed Direct Aldol Reactionsmentioning
confidence: 99%